Surgical technique and short-term outcomes in esophageal squamous cell carcinoma : A single center experience (Annals of Medical Research, 2021)
Aim: Esophagus cancers are the 8th most commonly seen cancers worldwide and the 6th cause of cancer-related mortality. By the time they are diagnosed they are generally not resectable and therefore have a poor prognosis. This is a complex disease that requires a multi-disciplinary approach. Apart from early stage tumors, surgery is recommended following chemoradiotherapy. Squamous cell carcinomas are seen more frequently and several surgical methods are applied for curative resection. The aim of this study was to present the surgical techniques applied to patients who underwent surgery for esophagus squamous cell carcinoma and to discuss the postoperative outcomes. Material and Methods: A retrospective review was made of the records of 14 patients with esophagus squamous cell carcinoma who underwent surgery in Samsun Training and Research Hospital between June 2016 and September 2018. Patients’ demographic data, diagnoses, tumor characteristics, postoperative complications, mortality, and clinical findings during follow-up were recorded.Results: The study included 14 patients, comprising 9 females and 5 males with a median age was 65.3 years (range, 39-80 years). Transhiatal esophagectomy was applied to 12 patients and thoraco-laparoscopic (TL) esophagectomy to 2 patients. No intra-operative complications developed in the patients applied with TL esophagectomy. In 3 of the patients applied with transhiatal esophagectomy, pneumothorax developed. No early or late postoperative complications developed in the patients applied with TL esophagectomy. In the transhiatal esophagectomy group, anastomosis leakage was observed in 2 patients and wound site infection in 1. The median length of hospital stay was 14 days (range, 7-39 days), and median postoperative follow-up was 12.5 months (range, 4-22 months). Conclusion: Despite small number of patients and short follow up, our study suggest that surgery-related morbidity and mortality will be lower in minimally invasive esophagectomy.Keywords: Surgical technique; esophagus; squamous cell carcinoma.
Keywords: Surgical technique; esophagus; squamous cell carcinoma.